TEACHING UKRAINIAN AS A NON-NATIVE LANGUAGE TO NATIONAL MINORITIES IN UKRAINE: CHALLENGES FOR EVIDENCE-BASED EDUCATIONAL POLICIES - Oksana Zabolotna; Svitlana Shchudlo; Tetiana Medina; Ielyzaveta Panchenko; Dmytro Kozlov (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2019)
Underachievement among national minority group students in places of their compact residence in Ukraine makes them vulnerable to educational failure. This problem is noticeable in Chernivtsi Region of Ukraine where the multicultural character causes peculiar behaviour in politics, migration, economic and cultural activities as well as in educational strategies. Owing to the fact that in some districts (Hertsa and Novoselica) the Ukrainian Language is not the mother tongue for most residents who are ethnical Romanians and Moldavians, about 60 % students fail in Independent External Testing after secondary school. This issue was taken into account in Article 7 of Ukrainian Law on Education (2017) which presupposed gradual significant growth in school subjects with Ukrainian as the language of instruction. The issue raised the research question: What approaches can be applied to teaching Ukrainian as a non-native language to national minorities in sites of their compact residence (where more than 80 % of the population speak Romanian in their everyday life)? This actualised the need for formulating evidence-based language policies in Ukraine. With the purpose of answering the need, Ukrainian Educational Research Association designed and carried out a public perception survey using in-depth interviews with high-school students and their parents, school teachers, local and regional policy-makers in education, local authorities, and national cultural societies. Based on the research, the authors give recommendations on approaches which should be used in design of curriculum and syllabus of Ukrainian as a non-native language. The authors emphasise the importance of the gradual introduction of the Ukrainian language starting from learning it as a foreign language at initial stages, with further switching to second language teaching strategies, and leading to bilingual education.